Interleukin-7 receptor α mutational activation can initiate precursor B-cell acute lymphoblastic leukemia - Almeida, Afonso R. M.; Neto, João L.; Cachucho, Ana; Euzébio, Mayara; Meng, Xiangyu; Kim, Rathana; Fernandes, Marta B.; Raposo, Beatriz; Oliveira, Mariana L.; Ribeiro, Daniel; Fragoso, Rita; Zenatti, Priscila P.; et al. (Nature communications, 2021)
Interleukin-7 receptor α (encoded by IL7R ) is essential for lymphoid development. Whether acute lymphoblastic leukemia (ALL)-related IL7R gain-of-function mutations can trigger leukemogenesis remains unclear. Here, we demonstrate that lymphoid-restricted mutant IL7R , expressed at physiological levels in conditional knock-in mice, establishes a pre-leukemic stage in which B-cell precursors display self-renewal ability, initiating leukemia resembling PAX5 P80R or Ph-like human B-ALL. Full transformation associates with transcriptional upregulation of oncogenes such as Myc or Bcl2 , downregulation of tumor suppressors such as Ikzf1 or Arid2 , and major IL-7R signaling upregulation (involving JAK/STAT5 and PI3K/mTOR), required for leukemia cell viability. Accordingly, maximal signaling drives full penetrance and early leukemia onset in homozygous IL7R mutant animals. Notably, we identify 2 transcriptional subgroups in mouse and human Ph-like ALL, and show that dactolisib and sphingosine-kinase inhibitors are potential treatment avenues for IL-7R-related cases. Our model, a resource to explore the pathophysiology and therapeutic vulnerabilities of B-ALL, demonstrates that IL7R can initiate this malignancy. Interleukin-7 receptor alpha (IL7Ra) is important for lymphoid cell development but its role in leukaemogenesis is not clear. Here, the authors generate a knock-in murine model to show that activating mutations in IL7Ra can initiate precursor B-cell acute lymphoblastic leukaemia.